Pengaruh Person Organization Fit Dan Komitmen Organisasi Terhadap Organizational Citizenship Behavior di PT Kereta Api Indonesia (PERSERO) - Endri Haryati; Agus Purbo Widodo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Person-organization fit is defined as the alignment between the values of the organization and the values of the individual. Person-organization fit refers to the compatibility of an employee with their organization. Person-organization fit has been defined in various ways, including value congruence, goal congruence, and the match between employee needs. Organizational commitment is defined as an employee's attachment to a particular organization, its goals, and their desire to maintain membership within the organization. Citizenship Behavior (OCB) is a term used for employees who provide added value to their assigned tasks as well as additional benefits to the company. PT Kereta Api Indonesia (Persero), hereinafter abbreviated as KAI or